2020
DOI: 10.1039/d0py00281j
|View full text |Cite
|
Sign up to set email alerts
|

Multi-photon polymerization of bio-inspired, thymol-functionalized hybrid materials with biocompatible and antimicrobial activity

Abstract: Thymyl-methacrylate functionalized, hybrid 3D scaffolds, fabricated by multi-photon lithography, exhibit excellent biocompatibility and antimicrobial action for bone and dental tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…These silicate-based materials, characterized by an inorganic (-Si-O-Si-) backbone functionalized with organic groups such as acrylates or epoxides, have been traditionally used for photonics [ 37 ], but they are now attracting interest for biotechnological applications. The organic side chains cross-link the resin into a durable and biocompatible solid material [ 39 , 40 ]. Always based on silicate materials, polydimethylsiloxane (PDMS) [ 41 ] is a widely used material to build microfluidic systems and micro-optics [ 42 ] that can be polymerized by means of MPA.…”
Section: Light Interaction With Soft Mattermentioning
confidence: 99%
“…These silicate-based materials, characterized by an inorganic (-Si-O-Si-) backbone functionalized with organic groups such as acrylates or epoxides, have been traditionally used for photonics [ 37 ], but they are now attracting interest for biotechnological applications. The organic side chains cross-link the resin into a durable and biocompatible solid material [ 39 , 40 ]. Always based on silicate materials, polydimethylsiloxane (PDMS) [ 41 ] is a widely used material to build microfluidic systems and micro-optics [ 42 ] that can be polymerized by means of MPA.…”
Section: Light Interaction With Soft Mattermentioning
confidence: 99%
“…The best-known example is two-photon stereolithography (TPS). The use of TPS in molecular imprinting is relatively new, even though the technique has already been reported in several different applications such as scaffolding for cells, , shape-shifting of microstructures for proteins, biocompatible hybrid materials, tomography, and optics. , This technique was first applied to the synthesis of MIPs by Chia Gomez et al, who showed its versatility by fabricating different structures such as grids, dot arrays and cantilevers smaller than 60 μm (Figure ). Lucirin TPO was used as a photoinitiator for a laser wavelength of 800 nm.…”
Section: Photostructuring Mipsmentioning
confidence: 99%
“…amino acids, and include primary amine (-NH 2 ), carboxylic acid (-COOH), thiol (-SH), and carbonyl (-CHO) functionalities. Complex microstructures have been already produced from modified thymol [177], cellulose-based compounds [178], functionalized gelatin and chitosan blends [176], silk-based compounds [179,180], hyaluronic acid [181], and dextran derivatives [182]. Even photoinitiator-free systems of biobased materials [44,45] were applied in MPL technology, which has made it possible to eliminate toxic photoinitiators commonly used in photo cross-linking reactions.…”
Section: Renewablesmentioning
confidence: 99%
“…The functionalization of materials used for 3D structuring by MPL has been studied for biomedical applications. Functionalization with proteins [230] and thymol [177] are only two examples that have been reported very recently.…”
Section: Functionalizedmentioning
confidence: 99%